Rare Variants in Known Susceptibility Loci and Their Contribution to Risk of Lung Cancer - Liu, Yanhong; Lusk, Christine M; Cho, Michael H; Silverman, Edwin K; Qiao, Dandi; Zhang, Ruyang; Scheurer, Michael E; Kheradmand, Farrah; Wheeler, David A; Tsavachidis, Spiridon; Armstrong, Georgina; Zhu, Dakai; et al. (Journal of thoracic oncology, 2018)
BACKGROUND: Genome-wide association studies are widely used to map genomic regions contributing to lung cancer (LC) susceptibility, but they typically do not identify the precise disease-causing genes/variants. To unveil the inherited genetic variants that cause LC, we performed focused exome-sequencing analyses on genes located in 121 genome-wide association study-identified loci previously implicated in the risk of LC, chronic obstructive pulmonary disease, pulmonary function level, and smoking behavior. METHODS: Germline DNA from 260 case patients with LC and 318 controls were sequenced by utilizing VCRome 2.1 exome capture. Filtering was based on enrichment of rare and potential deleterious variants in cases (risk alleles) or controls (protective alleles). Allelic association analyses of single-variant and gene-based burden tests of multiple variants were performed. Promising candidates were tested in two independent validation studies with a total of 1773 case patients and 1123 controls. RESULTS: We identified 48 rare variants with deleterious effects in the discovery analysis and validated 12 of the 43 candidates that were covered in the validation platforms. The top validated candidates included one well-established truncating variant, namely, BRCA2, DNA repair associated gene (BRCA2) K3326X (OR = 2.36, 95% confidence interval [CI]: 1.38-3.99), and three newly identified variations, namely, lymphotoxin beta gene (LTB) p.Leu87Phe (OR = 7.52, 95% CI: 1.01-16.56), prolyl 3-hydroxylase 2 gene (P3H2) p.Gln185His (OR = 5.39, 95% CI: 0.75-15.43), and dishevelled associated activator of morphogenesis 2 gene (DAAM2) p.Asp762Gly (OR = 0.25, 95% CI: 0.10-0.79). Burden tests revealed strong associations between zinc finger protein 93 gene (ZNF93), DAAM2, bromodomain containing 9 gene (BRD9), and the gene LTB and LC susceptibility. CONCLUSION: Our results extend the catalogue of regions associated with LC and highlight the importance of germline rare coding variants in LC susceptibility.
Keywords: dospělí; senioři nad 80 let; Humans; lidé středního věku; Lung Neoplasms; Aged, 80 and over; Middle Aged; celogenomová asociační studie; genetická variace; Risk Factors; mužské pohlaví; nádory plic; Susceptibility loci; Adult; rizikové faktory; ženské pohlaví; Genetic Variation; lidé; Exome sequencing; Genome-Wide Association Study; Lung cancer; Aged; senioři; Male; Rare variants; Female